Experimental Characterization of Sound Absorption for Composite Panel Made of Perforated Plate and Membrane Foam Layer - TRINH, Van-Hai; HE, Mu (Archives of Acoustics, 2025)
A recent key challenge in noise engineering is the development of structures or materials that achieve desirable acoustic performance in practical settings. Combinations of porous layers and perforated plates offer potential composite absorbers for various acoustic applications. The present work conducts experimental characterizations of sound absorption performance of absorbers based on membrane foams combined with perforated plates. Membrane foams with the well-controlled cell size and porosity are fabricated by milli-fluidic tools, whereas perforated plates are made within a tuned perforation ratio. The three-microphone method is used to perform the acoustic measurements. The results obtained from ten combination samples reveal that the sound absorption behavior of the foam-based layers can be successfully tailored and improved by a thin perforated plate within a reasonable hole diameter and spacing while maintaining the total thickness of the composite absorber.